Unified control infrastructure for carrier network evolution. - Hache, L. (IEEE Communications magazine)
Migration strategies for the network control infrastructure are discussed, to evolve carrier networks toward an optical transport backbone optimized for IP traffic. The strategies presented aim to protect carriers' investments in their current multiservice and IP-routed networks, while expediting the backbone migration toward a unified packet-over-optical core for IP and multiservice transport. This unified core network simplifies the network layers and control systems, and consolidates data and multiservice traffic to reduce network cost with improved bandwidth efficiency. The network control system, including signaling, addressing, and routing, is analyzed in detail to demonstrate the feasibility of the proposed infrastructure. Built on multiprotocol label switching (MPLS) technology, the presented solutions take phased evolution steps to reduce network cost, improve bandwidth efficiency, and offer practical options for internetworking during the migration. These solutions provide carriers with competitive advantages to consolidate multiple services onto an IP-centric optical transport network. The unified control infrastructure not only offers flexible options for network upgrade with reduced network management overhead, but also supports enhanced networking and traffic engineering capabilities to ensure no compromise in the service level agreement committed to end customers.